A STUDY OF SOME NON GENETIC FACTORS AND GENETIC PARAMETERS OF BODY WEIGHTS, DIMENSIONS AND FAT TAIL DIMENSIONS OF AWASSI SHEEP - Faris Y.Abdul-Rahman (Mesopotamia Journal of Agriculture)
The study included 276 records of Awassi lambs born in two flocks during the lambing season 2007 and 2008 and were maintained at College of Agriculture and Forestry Station, University of Mosul, and Animal Breeding Station , Mosul Al-Rashedia . The traits studied were: birth weight, body weight, body and fat tail dimensions at weaning (4) , 6 and 8 months of age . Heritability estimates for body weights at birth and 4, 6 and 8 months of age were 0.26, 0.33, 0.44 and 0.49, respectively. Heritability estimates for body and fat tail dimensions ranged between (0.11- 0.31), (0.16 – 0.48) and (0.27– 0.50) at 4, 6 and 8 months of age respectively. Most estimates of genetic correlations between body weights and body – fat tail dimensions and between each other were positive and heigh, and ranged between (0.19- 0.98) . Phenotypic correlations between traits studied ranged between (0.29 -0.98) at different ages. In general, The highest estimates for genetic and phenotypic correlations between traits studied were recorded at 6th month of age.